2012
DOI: 10.14214/sf.922
|View full text |Cite
|
Sign up to set email alerts
|

Forest planning in a Swedish company – a knowledge management analysis of forest information

Abstract: Forest data and forest information are central to forest management planning. The knowledge a large forest-owning company possesses about its forests could potentially be a strategic capability. In this study, the forest-planning process of a large forest company is analyzed in terms of knowledge management (KM). The study was conducted as a case study of Sveaskog -the largest forest-owning company in Sweden. The study focuses on the long-term harvest strategy through medium-term planning until the stands are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Similar studies that have suggested management zoning as an introductive framework for management come from Sweden [106][107][108], the Czech Republic [109][110][111][112], and Poland [19,[113][114][115]. Forest zoning consists of separating the land base into different management zones to address specific objectives; for example, conservation zones, intensive production zones, or even unmanaged zones (Figure 7).…”
Section: Description Of the Structure For Management Planning Zonesmentioning
confidence: 99%
“…Similar studies that have suggested management zoning as an introductive framework for management come from Sweden [106][107][108], the Czech Republic [109][110][111][112], and Poland [19,[113][114][115]. Forest zoning consists of separating the land base into different management zones to address specific objectives; for example, conservation zones, intensive production zones, or even unmanaged zones (Figure 7).…”
Section: Description Of the Structure For Management Planning Zonesmentioning
confidence: 99%
“…They use a hierarchical planning system that is based on a long-term plan (also known as the harvest estimation or strategic plan), a medium-term plan (or tactical plan) and a short-term plan (or operative plan), as shown in Figure 1 [3,4]. This planning hierarchy was introduced by the industrial forest companies in the 1960s and remains in use today [5,6]. The conceptual planning system is seen as a consecutive sequence of decisions in which the range of available options at any one stage is defined by the choices made in the preceding stages.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The planners were asked to rate the statement: "I do not want to put compartments into the TB if the information on their volume or assortment distribution is inaccurate". Their ratings of this statement were as follows: not at all, 7% (6), to some extent, 16% (14), quite a lot, 22% (19), totally, 47% (40), n/a, 7% (6). Figure 6 shows the harvest managers' ratings of the trustworthiness of the data in the TB on the availability of passable roads in each compartment.…”
Section: The Information Within the Tbmentioning
confidence: 99%
“…Methods for addressing multi-criteria decision-making processes and group decision making efforts have also been reviewed [11]. Other recent reviews include assessments of the value of participatory planning approaches in forest management [3,5,12], the incorporation of risk and uncertainty into forest planning [5], the availability and characteristics of decision support systems for forest management purposes [4••, 13, 14] and the lessons learned from the development of these tools [15•], the use of knowledge management tools, approaches and methods [16][17][18] and other computerised tools [19] associated with forest management decision-making processes. Optimisation processes are often, in fact, key components of decision support systems [20].…”
Section: Introductionmentioning
confidence: 99%